Arquivos da memória colonial portuguesa: o Arquivo Histórico Ultramarino, 1931-1974 - Gautier Garnier (Ler História)
The Arquivo Histórico Ultramarino (Overseas Historical Archive) was set up in 1931, as part of the Ministry of Colonies, to bring together in Lisbon all the archives relating to Portuguese colonial empire. The institution took on particular importance with the imperial policy of the Salazarist regime, as the mass of papers produced by the administration continued to grow. The AHU is studied from the point of view of the documentary issue, which had become an administrative problem. Assembling the empire’s papers in a single archive quickly proved to be a conflictual undertaking, with other institutions refusing to hand over their archive collections. In addition, the creation of the AHU forced the authorities to think about the circulation of documents within the empire. The use of microfilm made it possible to overcome the absence of certain originals in Lisbon. The structural lack of space raises the question of what constitutes a historical archive.